Respuesta :

x is [tex]\frac{11}{3}[/tex]

Step-by-step explanation:

Let us revise some rules of exponents

  • [tex](a^{n})(a^{n})=a^{m+n}[/tex]
  • [tex]\frac{a^{m}}{a^{n}}=a^{m-n}[/tex]
  • [tex](a^{m})^{n}=a^{mn}[/tex]
  • [tex]a^{m}=a^{n}[/tex] , then m = n

∵ [tex]27^{x-1}=9^{3x-7}[/tex]

- Factorize 27 and 9

∵ 27 = 3 × 3 × 3

∴ 27 = 3³

∵ 9 = 3 × 3

∴ 9 = 3²

Substitute them in the equation

∴ [tex](3^{3})^{x-1}=(3^{2})^{3x-7}[/tex]

- Use the third rule to simplify each side

∴ [tex](3)^{3x-3}=(3)^{6x-14}[/tex]

- Use the fourth rule

∵ The bases of the two sides are equal

∴ Their exponents are equal

∴ 3x - 3 = 6x - 14

- Subtract 6x from both sides

∴ -3x - 3 = -14

- Add 3 to both sides

∴ -3x = -11

Divide both sides by -3

∴ x = [tex]\frac{11}{3}[/tex]

x is [tex]\frac{11}{3}[/tex]

Learn more:

You can learn more about equations in brainly.com/question/4934417

#LearnwithBrainly